Needs assessment and preparatory work for addiction science programs at universities: experiences of universities in South Africa. - Kader, Rehana; Govender, Rajen; Cornelius, Warren; Abrahams, Lameze; Ashburner, Fergus; Tisaker, Nurain; Miovský, Michal; Harker, Nadine (Journal of Substance Use, 2024)
Background: This paper discusses the results from the first formal needs assessment conducted in South Africa to identify university curriculum development needs for addiction science training, particularly Substance Use Disorders (SUDs). Aim: The aim of the study was to report on the current addiction science curricula available at South African universities, educator views on the need for a new specialized addiction science curriculum, and the feasibility of implementing such a curriculum. Method: A 33 item electronic survey was emailed to respondents. Results: There is no standardization in SUD curriculum content and training at South African universities. Academic staff responsible for offering SUD training and curriculum development pedagogies in addiction are inadequately trained with a lack of content expertise. The absence of clear accreditation and certification standards and protocols results in graduates of varying competency levels and no registration as an addiction professional. Conclusion: Standardized academic training in addiction science is crucial for the professionalization of an addiction workforce.